Aggregatibacter actinomycetemcomitans Induces Autophagy in Human Junctional Epithelium Keratinocytes - Emiliano Vicencio; Esteban M. Cordero; Bastián I. Cortés; Sebastián Palominos; Pedro Parra; Tania Mella; Constanza Henrríquez; Nelda Salazar; Gustavo Monasterio; Emilio A. Cafferata; Paola Murgas; Rolando Vernal; et al. (Cells, 2020)
The adverse environmental conditions found in the periodontium during periodontitis pathogenesis stimulate local autophagy responses, mainly due to a continuous inflammatory response against the dysbiotic subgingival microbiome. The junctional epithelium represents the main site of the initial interaction between the host and the dysbiotic biofilm. Here, we investigated the role of autophagy in junctional epithelium keratinocytes (JEKs) in response to Aggregatibacter actinomycetemcomitans or its purified lipopolysaccharides (LPS). Immunofluorescence confocal analysis revealed an extensive nuclear translocation of transcription factor EB (TFEB) and consequently, an increase in autophagy markers and LC3-turnover assessed by immunoblotting and qRT-PCR. Correspondingly, challenged JEKs showed a punctuate cytosolic profile of LC3 protein contrasting with the diffuse distribution observed in untreated controls. Three-dimensional reconstructions of confocal images displayed a close association between intracellular bacteria and LC3-positive vesicles. Similarly, a close association between autophagic vesicles and the protein p62 was observed in challenged JEKs, indicating that p62 is the main adapter protein recruited during A. actinomycetemcomitans infection. Finally, the pharmacological inhibition of autophagy significantly increased the number of bacteria-infected cells as well as their death, similar to treatment with LPS. Our results indicate that A. actinomycetemcomitans infection induces autophagy in JEKs, and this homeostatic process has a cytoprotective effect on the host cells during the early stages of infection.